Influence of 3D Scanning Data Scattering to Volume Measurement of Horizontal Fuel Tanks - Knyva, V.; Knyva, M. (Elektronika ir Elektrotechnika, 2014)
Calibration of the fuel tanks must be made once in a 5 years. For calibration of the fuel tank 3D laser scanning and data processing method can be used. This article describes the influence of 3D laser scanning data scattering to volume measurement of horizontal fuel tank by means of relative error. It describes how to eliminate data scattering effects using filtering. DOI: http://dx.doi.org/10.5755/j01.eee.20.5.7102